Effects of N-acetyl cysteine on TRPM2 expression in kidney and liver tissues following malathion intoxication - Atilgan, Fethi Ahmet; Atescelik, Metin; Yilmaz, Mustafa; Turk, Ahmet; Gurger, Mehtap; Goktekin, Mehmet Cagri; Kuloglu, Tuncay (Taylor & Francis Ltd, 2022)
We investigated the effects of N-acetyl cysteine (NAC) on transient receptor potential melastatin 2 (TRPM2) channel expression in rat kidney and liver tissues following experimental malathion intoxication. We used seven groups of six male Wistar albino rats: control group, NAC, pralidoxime + atropine, malathion, malathion + pralidoxime + atropine, malathion + pralidoxime + atropine + NAC, and malathion + NAC. Single doses of 100 mg/kg N-acetyl cysteine, 40 mg/kg pralidoxime, 2 mg/kg atropine and 1/3 the lethal dose of malathion were administered. No difference in malondialdehyde (MDA) levels, apoptosis or TRPM2 immunoreactivity was found in liver tissue among the groups. In kidney tissue, MDA levels, apoptosis and TRPM2 immunoreactivity were increased significantly in the malathion and malathion + NAC groups compared to the control group. We found that organophosphate intoxication did not affect MDA, apoptosis or TRPM2 immunoreactivity in rat liver during the acute period. By contrast, we found that in kidney tissue, MDA, apoptosis, and TRPM2 immunoreactivity were increased significantly following administration of malathion. Also, NAC given in addition to pralidoxime and atropine reduced MDA to control levels.
Keywords: Kidney; liver; malathion; malondialdehyde; N-acetyl cysteine; organophosphates; rats; TRPM2